Sol-gel sulphated silica as a catalyst for glycerol acetylation with acetic acid - Ghoreishi, khadijeh beigom (Journal of Science and Technology, 2013)
This paper reports on the impact of sol-gel sulphated silica (SS), used as a solid acid catalyst in the esterification of glycerol with acetic acid. The effects of time, temperature, and molar ratio of acetic acid to glycerol were evaluated in order to optimize the reaction conditions for achieving a high monoacetin yield. A series of catalysts were prepared, with different loading percentages from 5 to 20 wt.%. The obtained sulphated silica had high specific surface area, in the range of 330-720 m2g-1. The results indicated that, the catalytic activity (acidic properties) increased with the amount of sulphuric acid loaded into the silica. In fact, the SS20 showed the highest catalytic activity, when using a reaction temperature of 50°C, and a glycerol to acetic acid mole ratio of 6 in 6h. Meanwhile all the catalysts showed a favorable selectivity to monoacetin.